2020
DOI: 10.1186/s12936-020-03324-3
|View full text |Cite
|
Sign up to set email alerts
|

Keep the quality high: the benefits of lot testing for the quality control of malaria rapid diagnostic tests

Abstract: Background The production and use of malaria rapid diagnostic tests (RDTs) has risen dramatically over the past 20 years. In view of weak or non-existing in vitro diagnostics (IVD) regulations and post-marketing surveillance (PMS) systems in malaria endemic countries, the World Health Organization, later joined by the Foundation for Innovative New Diagnostics, established an independent, centralized performance evaluation and Lot Testing (LT) programme to safeguard against poor quality of RDTs bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…On the other hand, it is still possible that quality variations between different RDT products and lots produced the higher RDTpfPR. 68 Despite the limitations of RDT, in the present study, the data of RDT still indicated the effectiveness of PBO-LLINs.…”
Section: Discussionmentioning
confidence: 48%
“…On the other hand, it is still possible that quality variations between different RDT products and lots produced the higher RDTpfPR. 68 Despite the limitations of RDT, in the present study, the data of RDT still indicated the effectiveness of PBO-LLINs.…”
Section: Discussionmentioning
confidence: 48%
“…In addition, a pre-procurement lot testing program checked the quality of each RDT lot procured by major donor organizations as well as country programs. 7 These two activities ensured that RDTs used in endemic countries were of good quality and led to an overall improvement in RDT performance, with the percentage of RDT products meeting WHO procurement criteria increasing from 26.8% to 79.4% between 2008 and 2018. 6,7 RDT performance evaluation is now incorporated into the WHO Pre-Qualification of in vitro diagnostics scheme and pre-procurement lot testing is currently not performed on all procurements but rather on an ad-hoc basis based on procurers' policies and practices.…”
Section: Quality Assured Rdtsmentioning
confidence: 99%
“…The programme was discontinued in 2019, and quality evaluations of RDTs were absorbed by the WHO Prequalification programme. The Prequalification programme will continue to conduct rigorous quality testing and make data on individual RDT performance available, however will no longer publish composite tables comparing RDT quality across products [ 13 , 23 ]. The results of these evaluations principally provide data on each RDT product’s panel detection scores as a measure of quality (see definition in Methods section) for both Plasmodium falciparum and Plasmodium vivax detection, as well as false positive rates, thermal stability, and ease of use, among other RDT characteristics.…”
Section: Malaria Rdt Procurement and Manufacturingmentioning
confidence: 99%